The Character Analysis in Ernest Hemingway’s Novel “The Old Man and The Sea” - Fitra, Muh. Al Fachrizah; Soghirun, Muh.; Nurul Hikmah Ramadhani (Journal of English Language Teaching, Literature and Culture, 2024)
This study examines the characteristics of the major and minor characters in Ernest Hemingway's novel The Old Man and the Sea. Employing a qualitative descriptive design, the research delves into the portrayal of human traits through the novel's characters. The findings reveal that Hemingway skillfully encapsulates various human qualities and struggles in his characters. Santiago, the protagonist, embodies perseverance and resilience despite facing prolonged adversity going eighty-four days without catching a fish. His eventual capture of the Marlin, a massive eighteen-foot-long fish, represents not just a personal victory but also the relentless struggle against forces beyond his control, as he ultimately loses the Marlin. Manolin, a minor character, is depicted as a loyal and compassionate boy who supports and cares deeply for Santiago. Their bond is marked by mutual respect and a shared passion for baseball, highlighting themes of mentorship, friendship, and intergenerational connection. Through these characters, Hemingway portrays the universal human experience of determination, loss, and the enduring strength of relationships.